A Quantile Regression Approach to Equity Premium Prediction. (15th September 2014) - Meligkotsidou, Loukia; Panopoulou, Ekaterini; Vrontos, Ioannis D.; Vrontos, Spyridon D.
ABSTRACT We propose a quantile regression approach to equity premium forecasting. Robust point forecasts are generated from a set of quantile forecasts using both fixed and time‐varying weighting schemes, thereby exploiting the entire distributional information associated with each predictor. Further gains are achieved by incorporating the forecast combination methodology into our quantile regression setting. Our approach using a time‐varying weighting scheme delivers statistically and economically significant out‐of‐sample forecasts relative to both the historical average benchmark and the combined predictive mean regression modeling approach. Copyright © 2014 John Wiley & Sons, Ltd.